The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/01658107.2017.1372488
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Melanoma of the Optic Nerve Sheath

Abstract: A 23-year-old man with a history of metastatic melanoma developed painful vision loss to counting fingers with enhancement of optic nerve on contrast-enhanced magnetic resonance imaging (MRI) and received a diagnosis of optic neuritis from an outside hospital. Despite empiric corticosteroid therapy, the patient worsened and developed secondary central retinal vein occlusion with further deterioration of vision. Repeat MRI demonstrated optic nerve sheath (ONS) involvement suggestive of optic perineuritis (OPN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There are also reports of optic nerve lymphoma and optic nerve sheath melanoma cases as serious compressive lesions mimicking ON. 34,35 About one third (36%) of the patients were eventually diagnosed with a disease other than ON and MRI especially aided in quick differentiation of ON from serious intracranial compressive lesions. Except the cases with intracranial expansion and one NAION patient who had optic disc swelling, MRI findings were unremarkable in patients who did not have ON.…”
Section: Other Diagnoses 21%mentioning
confidence: 99%
“…There are also reports of optic nerve lymphoma and optic nerve sheath melanoma cases as serious compressive lesions mimicking ON. 34,35 About one third (36%) of the patients were eventually diagnosed with a disease other than ON and MRI especially aided in quick differentiation of ON from serious intracranial compressive lesions. Except the cases with intracranial expansion and one NAION patient who had optic disc swelling, MRI findings were unremarkable in patients who did not have ON.…”
Section: Other Diagnoses 21%mentioning
confidence: 99%
“…Although the brain is one of the most common sites of metastatic melanoma (6), metastases to the optic nerve are exceedingly rare. A previous case reported optic nerve metastasis from metastatic melanoma, but this was in the context of known brain metastases (7). A 2008 systematic review found only 4 cases of cutaneous melanoma with optic disc or nerve metastases after long-term follow-up, all occurring in melanomas with a Breslow depth over 1.0 mm and with additional brain metastases (8).…”
Section: Discussionmentioning
confidence: 99%